Behavioral mutants of Drosophila melanogaster. - Homyk, T.; Szidonya, J.; Suzuki, D.T. (Molecular and General Genetics, 1980)
Sex-linked behavioral mutants were induced in Drosophila melanogaster with ethyl methanesulfonate (EMS) and isolated by direct visual observation of abnormal phenotypes. The four behavioral phenotypes used were flight-reduction, hyperactivity, hypoactivity and stress-sensitivity, and are easily discernable in either single or small populations of mutant flies. In one screen, forty-two behavioral mutants were recovered from strains derived from 800 mutagen-treated X chromosomes In a second screen, 139 behavioral mutants were obtained from 2369 X chromosomes. The high rate at which behavioral mutants were recovered in the second screen, when compared to new visibles (28) and new temperature-sensitive lethals (124), suggests that the isolation of behavioral mutations on the autosomes of Drosophila and in the genomes of larger insects should be practical.